SISTEM PENUNJANG KEPUTUSAN PENERIMA PROGRAM KELUARGA HARAPAN DENGAN MENGGUNAKAN METODE TOPSIS - Okta Jaya Harmaja; Maria Septina Hutauruk (Politeknik Bisnis Indonesia, 2021)
Currently poverty is still one of the problems faced by the people of Indonesia, based on data from the Central Statistics Agency (BPS), it is stated that the percentage of poor people in September 2019 was 9.22% or equivalent to 24.79 million people. One of the efforts that have been made by the Government to overcome the problem of poverty is the Family Hope Program (PKH). The program aims to break the chain or reduce the poverty index, increase human resources, and change behavior that is less supportive of improving the welfare of poor families. However, in its implementation there are still some problems that occur in the field, including the lack of a companion role, and some PKH recipients who are not on target, causing social suspicion. These problems can be overcome by using computer technology-based programs and still implementing transparent and accountable selection stages. In this study, the method used in the Decision Support System is the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method and the system is designed using the PHP programming language and MySQL database. With this program, it is hoped that the user as the PKH implementation committee can make data easier, determine quickly and efficiently and on target for determining recipients of PKH assistance.